The Developmental Implications of the Use of Reproductive Technologies for Transgender People: A Comparative Cross-Section Protocol - Mamou, Grégor; Lagrange, Chrystelle; Mendes, Nicolas; Wielart, Joy; Poirier, Fanny; Medjkane, François; Brunelle, Julie; Drouineaud, Véronique; Rosenblum, Ouriel; Gründler, Nouria; Ansermet, François; Falissard, Bruno; et al. (Frontiers in Psychiatry, 2020)
Today, couples with fertility issues can conceive thanks to biomedical technologies advances. Transgender persons cannot only actualize their self-identified gender identities but also experience parenthood [1]. However, some may question the welfare of the offspring because such transfamily forms are often confusing to many. The limited empirical research justifies more studies with evidence-based methodology to be conducted to assess whether or not these new ways of parenting have any adverse impact on children. The current report details the protocol we built in order to compare cognitive development, mental health, gender identity, quality of life and family dynamics in children from transgender father and donor sperm insemination (DSI) and two control groups matched for age and gender: typically developing (TD) children and children from cisgender parents and DSI. To calculate sample sizes, we hypothesize no significant difference between groups. Since 2008 transgender father can access DSI and have started conceiving children in France. They are proposed to engage in research to assess children well-being [2].The cohort includes 53 children in 37 families. We propose to carry out a cross-sectional comparative study exploring cognitive development with the Brunet-Lézine or the Wechsler’s Intelligence Scales according to age, mental health with the Child Behavior Checklist, gender identity with the GI-Interview for children, quality of life with the Kid-screen and the adolescent coping questionnaire, family dynamics with the Parental Bonding Instrument, the Inventory of Parent and Peer Attachment, the Five Minute Speech Sample, and Corman’s Family Drawing Test. To assess possible subtle differences between children’s family drawings, we will use a generalization of the “lady-tasting-tea” procedure to link qualitative and quantitative approaches [3]. 20 raters (4 child and family psychoanalysts, 4 adult psychiatrists , 4 biologist working in assistive reproduction technology , 4 endocrinologists working with transgender individuals and 4 students will be randomly shown the drawings and asked to blindly classify them according to whether the child had a transgender father using a Likert scale. Comparisons between the groups will be performed with appropriate statistical tests (Kruskal Wallis, ANOVA, Chi2 or Fisher exact test). For the “lady-tasting-tea” procedure we will use a permutation test.